Análisis psicométrico de la escala de ideación suicida de Roberts en universitarios mexicanos - Padrós-Blázquez, Ferran (Consorcio de Universidades Mexicanas A.C., 2022)
The observed increase in suicide rates in young people makes it necessary to develop screening scales to identify people at risk. A brief scale is the Roberts Suicidal Ideation Scale (EIS), showing good psychometric properties in Mexican adolescents. The objective of the present study was to corroborate the structure of said instrument through a Confirmatory Factor Analysis (CFA) and analyze its psychometric properties in university students. Applying a quantitative instrumental method, the EIS was administered to 1,190 university students. The results of the CFA corroborate the unifactorial structure of the EIS; likewise, the internal consistency reported with the ordinal Cronbach's alpha (αO = 0.813) was adequate. It is concluded that the instrument shows a unifactorial structure and that the psychometric characteristics of the reagents were adequate, highlighting that 2.9% of the sample obtained a score that indicates high suicidal risk.